Pengaruh Kerja Sama Tim, Disiplin Kerja, dan Etika Kerja Terhadap Kinerja Karyawan Pada Lotus Garden Hotel Kediri - Machsunah, Siti Untari; Akbar, Taufik; Syahputra, Erwin (Universitas Maritim AMNI Semarang, 2023)
This research is motivated by an agency operating in the hospitality sector, because in agencies human resources are very important in achieving success. The purpose of this research is to explain the influence of teamwork, work discipline, and work ethics on employee performance. The research method used is a quantitative method using questionnaires as data. This research uses a saturated sampling technique. The sample in this research was all PKWT employees, 47 employees of Lotus Garden Hotel Kediri. In this research, the results showed that teamwork partially had no significant effect on the performance of Lotus Garden Hotel Kediri employees, work discipline partially had a significant effect on the performance of Lotus Garden Hotel Kediri employees, and work ethics partially had an effect on the performance of Lotus Garden Hotel Kediri employees. Meanwhile, simultaneously these three variables have a significant effect on the performance of Lotus Garden Hotel Kediri employees.